- #1
Avatrin
- 245
- 6
(1) Given: b
(2) Suppose: a
(3) By implication with (2) and (1), a→b
I just saw this proof... And, I don't understand why this is true. How am I supposed to think about problems like this one?
Edit:
Here's another one:
The only steps here I understand are 1 to 5. I don't know why 6 and 7 are true.(1) Given: (p∧q)→r
(2) Suppose: p
(3) Suppose: q
(4) By conjunction with (2) and (3), p∧q.
(5) By MP with (1) and (4), r
(6) By implication with (3) and (5), (q→r)
(7) By implication with (2) and (6), p→(q→r)